Ossification Of The Posterior Longitudinal Ligament As A Predisposing Factor In Spinal Cord Injury: A Case Report - Tjahaja, Skolastika Beatrice; Congdro, Jessica; Atmadja, Andika Surya (Acta Neurologica Indonesia, 2025)
Introduction: Ossification of the posterior longitudinal ligament (OPLL) is a risk factor for SCI. It is found during imaging studies in approximately 30% SCI patients. SCI on OPLL patients can lead to neurological morbidity and significant reduction in quality of life if not treated adequately. Case Report: A 35-year-old female fell from the stairs. The head and neck were not hit during the incident, however patient complained of weakness in all extremities, especially in both legs, which was accompanied by tingling and numbness. Patient’s motor strength was 4555/5554+ and 3111/3222. There was also hypoesthesia at C5 level and below. The OPLL was found at level V.C1 through V.Th1, which impinged on thecal sac and spinal cord especially on V.C3 to V.C7. Spinal cord edema was also seen in cervical and lumbar segments. The patient was then given collar neck, intravenous methylprednisolone, and symptomatic treatments. After 1 week of treatment, the patient could stand and walk with assistance. After 2 months of routine physiotherapy, the patient could walk and do activities independently. Discussion: There are several factors affecting OPLL namely genetic, hormonal, and environmental factors. Increase in osteogenesis-triggering growth factors is also frequently found in OPLL patients. OPLL patients have higher risk of getting SCI during trauma. Pharmacology treatment can be combined with physiotherapy, orthosis usage, or surgery. Conclusion: Patients with OPLL are at risk of experiencing more severe symptoms in SCI events. Appropriate therapy and management of SCI in OPLL can improve patient morbidity rates. Keywords: SCI; OPLL; myelopathy